ANALISIS IMPLEMENTASI EMERGENCY RESPONSE PREPAREDNESS KEJADIAN KEBAKARAN DAN LEDAKAN PADA PENGELOLA BAHAN BAKAR RISIKO TINGGI X TAHUN 2023 - Farah Namira Anjani, (2024)
LPG terminals have complex operational activities consisting of receiving, distributing and storing flammable materials that can burn and explode. Emergency Response Preparedness (ERP) is important to anticipate emergencies, prevent the spread of hazards and reduce losses. This study was conducted to determine the application of ERP for fire and explosion events at LPG terminals based on the International Safety Rating System (ISRS). This research was a qualitative case study with in-depth interviews, observation and document review as data collection methods. Informants, including Incident Commander, On Scene Commander, Operation Commander and Sector Commander Fire Brigade were selected using by a purposive sampling technique. Data validation was based on source triangulation and method triangulation techniques. The results show that the company has implemented (91.4%) of ERP criteria. However, there are inadequacies in the aspects of support and cooperation from externals, medical support, protection systems and major accident preparedness. Emergency protection systems maintenance, automation systems, pre-hospital transport including an ambulance, response time criteria establishment and partnership agreements with external parties are recommended.